(untitled) (Research, Society and Development, 2022)
Introduction: Hospitalization is a critical process, with great repercussions for the family/child binomial. Objective: The study aimed to understand the impact of hospitalization on the family/child binomial and demonstrate how nursing care should be carried out in this context, aiming to improve the quality of care and reduce the negative impacts of this period. Methodology: For this, an integrative literature review was carried out, having as a guiding question: “What is the role of nursing in the care of hospitalized children, in order to contribute to reducing the impact of hospitalization?”. The searches were carried out in the online databases: Virtual Health Library (BVS) and Scientific Electronic Library Online (SciELO), in which the final sample of this review consisted of 9 scientific articles. Results and discussion: In debate, the hospitalization of the child causes critical impacts and a large proportion of the family, since it is the pillar of support for this individual and with this, numerous physical and emotional reactions are triggered. Conclusion: It is concluded that the impact generates marked changes both in family dynamics and in their routine, causing emotional and physical consequences for the child and family, making it clear the importance of strategies to overcome the negative effects of hospitalization in children and the importance of recommendations for promoting well-being.